(untitled) (Per Musi, 2017)
The practice of sonority experimentation on keyboards was the predominant trademark of the 17th and 18th centuries and various Preludes were written in order to reach this goal. They were later incorporated, as part of the duality Prelude and Fugue, and aimed at the improvisatory performance, but ended up perpetuating themselves in the following centuries as independent pieces. Beginning as a simple controlling activity for the tuning of a given instrument and/or its expressive capability, it established itself as a definite musical form in the many compositional styles and on different historical moments. It is curious to note in many Präludia the insertion of bar lines that, contrary to their freer nature, hinders their fluency and liberty. This study aims at the investigation of their genesis, at the end of the 16th century, their perpetuation in the following centuries up to this unusual Mozartian proposal.